Changes in Anxiety Control Beliefs Following a Brief CBT Treatment and Their Association With Anxiety Symptom Reduction. Issue 6 (November 2021) - Radtke, Sarah R.; Ollendick, Thomas H.; Weems, Carl F.
Highlights: Anxiety control beliefs were measured after a 3-hour treatment for specific phobias. Self-reported anxiety control beliefs significantly increased following treatment. Those increases significantly predicted reductions in specific phobia severity. They also predicted reductions in symptoms of comorbid anxiety disorders. These findings are particularly novel given the brief nature of the intervention. Abstract: Anxiety control beliefs (i.e., beliefs regarding one's ability to cope with external, fear-inducing threats and internal reactions to those perceived threats) have been found to negatively predict anxiety symptoms in children and adults and to be modifiable by cognitive-behavioral therapy for anxiety disorders. The current study examines whether changes in anxiety control beliefs were seen following a brief, intensive treatment for specific phobias, and whether those changes were associated with improvements in the targeted phobia and comorbid anxiety disorder symptoms. Participants were 135 children and adolescents ( M age = 9.01 years, 49% male) who received one-session treatment (OST) with or without parental involvement for their primary specific phobia. Results indicated that self-reported anxiety control beliefs significantly increased following treatment and that these increases significantly predicted reductions in specific phobia severity and symptoms of comorbid anxiety disorders 6 months and 1 year following treatment. Findings illustrate that involvement in a single 3-hour OST was associated with changes in anxiety control beliefs and demonstrate the potential importance of targeting control beliefs in pediatric anxiety treatment.